Nutrição mineral em plantas de copo de leite: deficiência de nutrientes e adubação silicatada - Almeida, Elka Fabiana Aparecida (2007)
The aspects related to mineral nutrition in ornamental plants are very important to the production of quality flowers. In the specific case of the calla lily (Zantedeschia aethiopica) the information on nutrition and manuring in commercial cultivations are quite incipient. Thus, the objectives of this work were to evaluate the deficiencies of nutrients and different concentrations of silicon in calla lily. Two experiments were arranged in a randomized block design with four replicates. In the first experiment calla lily seedlings were submitted to twelve treatments constituted in individual omission of N, P, K, Ca, Mg, S, Fe, B, Mn, Cu, Zn and one control. The concentrations of 25, 50, 75 and 100 mg dm-3 of silicon applied in the substrate of seedling cultivation and a control were studied in the second experiment. In the first experiment it was possible to evaluate the visible deficiency symptoms and the influence of the absence of the nutrients on development and nutritional status of the plants. Plants cultivated with omission of Cu and Zn were not evaluated, due solutions contamination on those treatments. The first deficiency symptoms were observed in plants submitted to the omission of N, followed by S, B, K, Fe, P and Ca. The P, S, Ca, N and B deficiencies affected more the development of the plants on the characters observed. The deficiencies of S and K provided the development of inflorescences of low quality when compared to the other treatments. It was observed that the nutritional deficiency influenced the content of the omitted elements and the content of the other nutrients in leaves, tubers, roots and inflorescences. In the second experiment it was observed that calla lily is not silicon accumulative. The use of potassium silicate increases the pH of the soil and the absorption of sulfur. The results showed that, for the severity of the deficiency symptoms, calla lily is quite demanding in N, B and S. Silicon fertilizer did not influence the calla lily development in the silicon concentration used.